KAJIAN PENGARUH KARAKTERISTIK SEDIMEN TERHADAP PROFIL PANTAI PASIR BUATAN DI BELAKANG STRUKTUR BAWAH AIR - , Endang Setyawati Hisyam, Prof. Ir. Nur Yuwono, Dip.H.E., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Damage of the beach has appeared material and life losses. Therefore, It needs beach protection with sand nourishment or artificial sandy beach. Its problems are the operation and maintenance relatively high cost and need borrow area to supply the sand requirement due to so much the sand loss. protection is needed to keep the sandy beach due to wave attack. Geotextile tube (geotube) as submerged breakwater is the one alternative as artificial beach protection due to erosion. This research aim to know the influence of the sediment characteristic to artificial sandy beach profile behind the structure. ( d The fisical model was conducted by way sediment variety are Krakal beach sand 50=0.433 mm), laboratory sand (d50=0.67 mm), and Tanjung Ann sand (d50=1.47 mm) Likewise, the height of the submerged structure is variated (Rc/hs: -0.28